The effects of different solubilizing agents on the transport and pharmacokinetic profiles of indomethacin: in vitro and in vivo approach - Siti Aisyah Zainuddin,; Abdul Latip Ab Hamid,; Aqila Iman Rafandi,; Mashani Mohamad,; Khuriah Abdul Hamid,; Syed Haroon Khalid, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The poor water solubility of new chemical entities (NCEs) discovered in pharmaceutical screening programs hampers their development and limits effective treatment delivery. Solubilizing agents offer a direct approach to increase solubility and oral bioavailability. This study employed indomethacin as a model drug from Biopharmaceutical Classification System (BCS) class II. Solubilizing agents, including propylene glycol, Transcutol P, Labrasol, PEG 400, and Tween 80, were separately added at 10% (v/v) to 1 mg/5 mL for in vitro diffusion chamber and 10 mg/kg body weight for in vivo oral absorption studies of indomethacin. Drug concentrations were analysed using reversed-phase high-performance liquid chromatography (HPLC). In vitro, 10% (v/v) labrasol, PEG 400, and Tween 80 significantly (p<0.01) increased indomethacin permeability across the rat intestinal layer. However, Transcutol P and PG (propylene glycol 10%v/v) showed no discernible impact on in vitro permeability. In the in vivo oral absorption study, PG (propylene glycol 10%v/v) and Transcutol P significantly (p<0.05) enhanced indomethacin absorption, while 10% (v/v) labrasol, PEG 400, and Tween 80 did not show significant effects. No in vitro-in vivo correlation (IVIVC) was observed, likely due to the physicochemical properties of indomethacin and the complex physiological environment in the gastrointestinal (GI) tract. Further investigations are necessary to comprehensively understand the factors affecting indomethacin solubility and absorption, considering both the drug’s properties and the GI tract’s physiological conditions.